HUBUNGAN PENGGUNAAN KB SUNTIK DEPO PROVERA 3 BULAN TERHADAP KADAR Hb PADA WUS WANITA USIA SUBUR DI BPM (BIDAN PRAKTEK MANDIRI) NUNI NURAENI KELURAHAN PADASUKA CIOMAS KABUPATEN BOGOR - Meirina Daulay; Kasih Purwati (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Family Planning is an acronym for Family Planning which was formed by the government to reduce the number of people using contraception, but some contraceptives have side effects namely bleeding, headache, nausea, menstrual disorders, weakness/fatigue, and vaginal discharge. This study was an observational analytic study with a cross-sectional design. Samples were all users of 3 months Depo Provera Injecting KB injection at BPM Nuni Nuraeni, Padasuka Ciomas, Bogor Regency in 2018. Statistical tests used chi-square. The results of univariate analysis showed WUS using Depo Provera injections 3 months 49 (65.3%) and WUS who did not use Depo Provera injections 3 months 26 (34.7%), WUS who used 3 months Depo Provera injectable KB obtained that Hb levels were normal 43 (57.3%) and whereas WUS who used KB injections Depo Provera 3 months found that Hb levels were not normal 32 (42.7%). In the Bivariate analysis, based on the results of the Chi-Square Statistical Test with a significance limit Î± = 0.05 and 95% CI obtained Ï value = 0.26 Î±> 0.05 (Prevalence Rate = 3,300). This shows that there is no relationship between the use of 3 months Depo Provera injecting contraception to Hb levels in WUS at BPM Nuni Nuraeni. Thus the hypothesis which states that there is a relationship between the use of 3 months Depo Provera injecting contraception with Hb levels in WUS is rejected. From the results of the study it can be concluded that there is no relationship between the use of a 3-month injection of Depo Provera injections with Hb levels in WUS at BPM Nuni Nuraeni, Padasuka Ciomas, Bogor Regency.